Characteristics of Candida albicans adherence to mouse tissues. - Cutler, J E (1990)
An ex vivo binding assay originally described for determining lymphocyte homing receptors was adapted for studying Candida albicans-host cell interactions in unfixed tissue sections. BALB/cByJ mice were sacrificed, and various organs were removed, rapidly frozen on dry ice, and sectioned. C. albicans yeast cells were suspended to 1.5 x 10(8) cells per ml in Dulbecco modified Eagle medium supplemented with 5% newborn calf serum, and 100 microliters of the suspension was added to tissue sections for 15 min with rotation at 4 degrees C or at 22 to 24 degrees C. The sections were then fixed in glutaraldehyde, washed, and examined. Stationary-phase yeast cells adhered better than log-phase cells, and adherence characteristics were similar at 4 degrees C and 22 to 24 degrees C. Yeast cells from nine strains of C. albicans showed similar tissue specificity. Adherence to lymph node tissue was confined to subcapsular spaces and trabecular sinuses. In the spleen, yeast cells bound to the marginal zones. In both tissues, an association of yeast cells with tissue macrophages was suggested by results with macrophage-specific monoclonal antibodies and fluorescent or immunoperoxidase staining techniques. C. albicans adhered to convoluted tubules, glomeruli, and the tunica media of arterioles in the kidney. During experimentally induced fungemia in mice, C. albicans yeast cells associated with the same tissue sites as in the ex vivo assay, except that binding to renal arterioles was not seen in the in vivo test. A strain of Saccharomyces cerevisiae showed some adherence patterns in common with C. albicans, which indicates that tissue adherence is not sufficient for virulence. Mechanisms of attachment were not determined, but strains of C. albicans varied quantitatively in their ability to attach, and binding was inhibited by chelators of divalent cations.